THE IMPACT OF ECONOMIC DIPLOMACY ON FOREIGN TRADE. EMPIRICAL EVIDENCE FOR THE EUROPEAN COUNTRIES - Cătălina BRATOSIN-VASILACHE; Liviu-George MAHA (EURINT, 2022)
Lately, economic diplomacy has been gaining attention in the empirical studies, many of them focusing on the contribution of the diplomatic service and emphasizing the relevance of diplomatic relations in boosting trade. Thus, quantitative research design, mostly based on the gravity model of international trade, is being applied in analyzing the impact of economic diplomacy on international trade or foreign direct investments. This paper aims to present a comprehensive perspective of the empirical studies that consider economic diplomacy as one of the determinants of foreign trade in the European countries. The findings of this paper suggest that economic diplomacy, through activities carried by diplomatic representations abroad, such as embassies, consulates and export promotion agencies, has a positive impact on foreign trade.